Application of Flipped Classroom and Teams Games Tournament Learning to Increase Motivation and Adaptive Physical Education Learning Outcomes - Syafrial Syafrial; Yahya Eko Nopiyanto; Arwin Arwin (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2022)
The level of motivation and learning outcomes of physical education students is still in the low category, especially in participating in adaptive physical education lectures. Therefore, an effective adaptive physical education learning design or model is needed so that learning objectives can be achieved optimally. The learning model demanded by students today is a learning model that is open, flexible, accessible to students wherever and whenever. For this reason, one alternative to overcome low motivation and learning outcomes is to combine the flipped classroom and team games tournament learning models. The research method used is classroom action research using two cycles consisting of planning, action, observation, and reflection. Instruments and data collection techniques used observation guides, questionnaires, and tests. Qualitative descriptive techniques are used to analyze the results of observations, while quantitative descriptive techniques are used to analyze the results of questionnaires and learning outcomes. Based on the results of data analysis, it can be seen that the application of flipped classrooms and team games tournaments can increase motivation and adaptive physical education learning outcomes.